Human fasciolosis in Van province, Turkey - Yilmaz, H; Göekmerdan, A (Elsevier, 2004)
This investigation was carried out to determine the frequency of the fasciolosis in Erci, a town in the Van province located in the Eastern Turkey. The study includes 500 asymptomatic subjects (322 males and 178 females) whose ages ranged from 5 to 75 years. In all subjects, stool samples were examined at initiation of the study and one week later to rule out pseudoparasitosis. The methods of flotation (in saturated saline solution) and sedimentation (in formalin-ether solution) were used in examination of the stool samples. Fasciola hepatica eggs were detected in nine (1.8%) out of 500 subjects. In conclusion, our data showed that the prevalence of human fasciolosis was high in our region because watercress consumption was common. We also think that human fasciolosis is more frequent than expected in Turkey. To determine the exact prevalence of the disease, extensive serological investigations should be performed in different regions of Turkey. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: coproparasitologic investigation; human fasciolosis; prevalence